Deep Vein Thrombosis Prophylaxis in Patients with Traumatic Brain Injury - Gomes da Silva, Vinícius Trindade (2015)
Introduction: The risk of deep vein thrombosis is increased in patients with head trauma, but the prophylaxis against this event is confronted with the possible risk of worsening hemorrhagic injuries. In this article, we present an overview about deep vein thrombosis prophylaxis in patients with head trauma and we propose a practical protocol for clinical management of deep vein thrombosis prophylaxis.Material and Methods: We reviewed relevant papers cited in the Medline/PubMed, Cochrane, and Scielo databases from January 1998 to January 2014. Based on a search with the following search expression: “deep venous thrombosis and prophylaxis and traumatic brain injury”, we found 44 eligible articles. Twenty-three papers were selected using criteria as published in English or Portuguese, patients in acute phase of moderate and severe traumatic brain injury and noninvasive mechanical prophylaxis or chemistry.Results: Head trauma alone is a risk factor for deep vein thrombosis. The chance of deep vein thrombosis is 2.59 times higher in patients with head trauma. The prevalence of deep vein thrombosis and pulmonary embolism in patients who have suffered head trauma is 20% in the literature, reaching 30% in some studies.Discussion and Conclusion: Head trauma alone is a risk factor for deep vein thrombosis and pulmonary thromboembolism and the risks inherent in this disease requires methods of prevention for these complications. Clinical trials are needed to establish the efficacy of prophylaxis and the best time to start medication for deep vein thrombosis in patients with traumatic brain injury.